Insights from a Cross-sectional Study on Nutritional Status in Children: Wawasan dari Studi Cross-sectional mengenai Status Gizi pada Anak - Debora Chandra Kirana; Hesty Widowati (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the relationship between diet, medical history, and nutritional status in 48 children aged 3-5 from Kindergarten Tegalasri Village, Blitar Regency. Using observational analysis with a cross-sectional approach, data on eating habits and medical records were collected. The results, analyzed using chi-square tests, indicated no significant correlation between diet or viral disease history and the children's nutritional status. These findings suggest that factors beyond diet and infections may play a more significant role in determining the nutritional status of children in this demographic, highlighting the need for further research and targeted interventions to promote better nutritional outcomes Highlight: Children's Nutrition: Diet and Medical History Impact on Well-being. Cross-sectional Study: Understanding Factors Influencing Nutritional Status in Young Children. Key Keywords: Nutrition, Children, Diet, Medical History, Cross-sectional Study. Keyword: Nutrition, Children, Diet, Medical History, Cross-sectional Study